Economic indices (Journal of Economic Research & Business Administration, 2016)
Indexes occupy an important place in the statistical analysis, they are often asked to work on the control statistics on indexes, they are generalizing indicators. Word index is translated from Latin means «pointer», «figure», «list». Index statistics is a relative index, which characterizes the change in the value of a phenomenon in time, space or over any standard. Or index, a measure of comparison of the two states of the same phenomenon. Unlike conventional relative values, which are calculated on the grounds of an isolated, indexes may include a system of signs. This means that the object index analysis and are structurally complex phenomenon. When analyzed by comparing the levels of the studied phenomenon in time, we speak about indexes dynamics in space - territorial indexes, and so on. D. The main element of the index ratio is indexed value, which is a characteristic value of a statistical population, a change which is the object of study.
Keywords: individual indices; the average index; general index; aggregate indices; the index of permanent (fixed) of the index of variable composition.